Penerapan project based learning untuk meningkatkan hasil belajar teks prosedur siswa SMP - Muhammad Singgih; Septia Uswatun Hasanah (Aksara: Jurnal Bahasa dan Sastra, 2023)
Writing is the most advanced language skill. It must be honed frequently in order to become skilled in writing. This study used the Classroom Action Research (PTK) method. PTK was conducted in 2 cycles and each cycle consisted of planning, implementation, observation, and reflection activities. The sample in this study was class VII C SMPN 35 Bandar Lampung as many as 27 people. The results of the increase in grades and the number of students passing above KKM in the pre-cycle process were 13 students (48.1%) completed the learning, in cycle I 18 students (67%) completed the learning and cycle II as many as 24 students (89%) completed the learning.Keywords: PTK, PBL, Prosedur Text